Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 13. Beitrag. Coleoptera: Scarabaeidae I (Dynastinae, Valginae und Trichiinae). - Schulze, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The above publication deals with the Dynastinae, Valginae and Trichiinae of Albania. Studying the material collected by the Albania-Expedition of the Deutsches Entomologisches Institut (38 specimens representing 5 species) by A. Bischoff (1932-1937), G. Friese (1959), and I. Grebenscikov (1958) there were found 4 species new to the fauna of Albania, which now contains 4 species of the Dynastinae, one of the Valginae and 5 of the Trichiinae. The number of species of Scarabaeidae known from this country is now 134. A new aberration of Trichius fasciatus (pseudoscutellaris ab. nov.) is described.